Exploring metacognitive strategy use during note-taking for students with learning disabilities. Issue 2 (3rd March 2016) - Boyle, Joseph R.; Rosen, Sonia M.; Forchelli, Gina
Abstract : This mixed-methods study analysed over 200 interviews from 20 seventh-grade students with learning disabilities (LD). Students were instructed how to use a note-taking intervention during science lectures. The interview analyses were supported by pre- and post-intervention quantitative data. Data suggest that the intervention helped students identify important information; systematised the process of listening to, interpreting and using that information; and offered students a means by which to organise the information they were hearing. A discussion about metacognition and attention explores how these processes altered students' awareness of their own learning, as well as how they equipped students with a new strategy for holding onto and translating information from their science lectures into a useful set of notes. These findings have implications for how theorists conceptualise the relationship between metacognition and attention and how teachers use scaffolding to support the learning of students with LD.